Effect of Service Quality on Customer Satisfaction at PT. PLN (Persero) Rayon Siborong Borong Sibolga Area - Romina L.D Sinaga; Leonard Roberto Sinaga (Institute of Computer Science (IOCS), 2021)
This study aims to determine and analyze how the influence of service quality on customer satisfaction at PT. PLN (Persero) Rayon Siborong Borong Sibolga Area. Data analysis method used is simple correlation analysis method, simple linear regression analysis and t test. The population in this study were all customers who use KWH (kilo watt hour) 1300va rates as many as 375 customers. The sample can be determined using the Slovin formula with an error rate of 10%. So the sample in this study was 79 people. The data obtained from questionnaires distributed to a sample of 79 people obtained a correlation with the results that rcount (0.611)> rtael (0.221) concluded that there was a significant relationship between service quality (X) and customer satisfaction (Y) at PT. PLN (Persero) Rayon Siborongborong Sibolga Area. Based on table 3.2 of the correlation coefficient interpretation guidelines, the coefficient found is 0.611 which means the strong category. So there is a strong relationship between service quality (X) and customer satisfaction at PT.PLN (Persero) Siborong Borong District Sibolga. R Square is 0.373. This shows that the impact of Service Quality (X) customer satisfaction (Y) at PT PLN (Persero) is 37.30% and the remaining 62.70% is influenced by other factors that are not discussed in this study. The regression equation is Y = 14.412 + 0.810X. Based on the regression equation above, it can be explained that if the Service Quality X = 0 then the value of customer satisfaction or Y will increase by 14,412. The significance of variable correlation is 6,774. Then the value is compared with t table with an error rate of 5% df = n-2 = 77. The t table value of (1.668) is in accordance with the requirements of testing the hypothesis that t (6.744)> t table (1.668) can be concluded that Service Quality (X) has a positive and significant effect on customer satisfaction (Y) at PT PLN (Persero). ) Siborong Borong Rayon then the research hypothesis is accepted.